Interactive effects of carbohydrate, lipid, protein composition and carbon/nitrogen ratio on biogas production of different food wastes - Xue, Shengrong; Wang, Yanbo; Lyu, Xingang; Zhao, Nan; Song, Jinghui; Wang, Xiaojiao; Yang, Gaihe (Bioresource technology, 2020)
•The range of proportions is lessened by considering C/N ratio and LCP composition.•The interaction of C/N ratio and LCP composition influence methane production.•Optimizing the C/N ratio and LCP composition can improve AD performance. The anaerobic co-digestion (AcoD) of FWs produces variable methane yields, mainly due to variable carbon/nitrogen (C/N) ratio and proportions of lipids (L), carbohydrates (C), and proteins (P) in different FW samples. In this study, a significant interaction between C/N ratio and LCP composition was found and contributed to the differing trends between special (SMP) and theoretical methane production. The highest SMP of 595 mL CH4 gVS−1 occurred at C/N of 25 and LCP of 63.25:22.62:14.13, followed by 592 mL CH4 gVS−1 at C/N of 30 and LCP of 48.94:39.74:11.32, which also reflected their interaction. Attributing to their interactive effect on obtaining optimal process parameters and microbial community, the inhibition threshold of lipid as well as the methane yield was increased. Understanding the interaction between C/N ratio and LCP composition is an effective and promising way to obtain suitable mixture ratios of organic wastes under AcoD.